Trends in Advanced Intelligent Control, Optimization and Automation Proceedings of KKA 2017-The 19th Polish Control Conference, Kraków, Poland, June 18-21, 2017 - Mitkowski, Wojciech; Kacprzyk, Janusz; Oprzędkiewicz, Krzysztof; Skruch, Paweł; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume contains the proceedings of the KKA 2017 - the 19th Polish Control Conference, organized by the Department of Automatics and Biomedical Engineering, AGH University of Science and Technology in Kraków, Poland on June 18-21, 2017, under the auspices of the Committee on Automatic Control and Robotics of the Polish Academy of Sciences, and the Commission for Engineering Sciences of the Polish Academy of Arts and Sciences. Part 1 deals with general issues of modeling and control, notably ﬂow modeling and control, sliding mode, predictive, dual, etc. control. In turn, Part 2 focuses on optimization, estimation and prediction for control. Part 3 is concerned with autonomous vehicles, while Part 4 addresses applications. Part 5 discusses computer methods in control, and Part 6 examines fractional order calculus in the modeling and control of dynamic systems. Part 7 focuses on modern robotics. Part 8 deals with modeling and identification, while Part 9 deals with problems related tosecurity, fault detection and diagnostics. Part 10 explores intelligent systems in automatic control, and Part 11 discusses the use of control tools and techniques in biomedical engineering. Lastly, Part 12 considers engineering education and teaching with regard to automatic control and robotics.
Sliding mode control of discrete time dynamical systems with state constraints -- Offset-free nonlinear model predictive control -- Simple example of dual control problem with almost analytical solution -- Lyapunov matrices approach to the parametric optimization of a time delay system with PID controller -- Estimation of control improvement benefit with α-stable distribution -- Stability analysis of a series of cars driving in adaptive cruise control mode -- The clipped LQ control oriented on driving safety of a half-car model with magnetorheological dampers -- Implementation of DMC algorithm in embedded controller - resources, memory and numerical modifications.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Control, Robotics, Automation; Control and Systems Theory